From human rights to international criminal law : studies in honour of an African jurist, the late Judge Laïty Kama = Des droits de l'homme au droit international pénal : etudes en l'honneur d'un juriste africain, feu le juge Laïty Kama (M. Nijhoff, 2007)
Judge Laïty Kama, the first president of the International Criminal Tribunal for Rwanda, died 5 years ago. He was a Senegalese Judge, and a Human Rights expert within the United Nations. This collection of essays on international criminal law and human rights is published to honour him. They are signed by his colleagues of the Arbitrary Detention Working Group or new members, Judges from the ad hoc Tribunals and the International Criminal Court, Lawyers and Jurists from different places. Deep analysis of various human rights issues and the jurisprudence of the international criminal court and tribunals are provided here, to reflect areas of interest to the late Judge Kama. Le juge Laïty Kama, premier président du Tribunal pénal international pour le Rwanda, est décédé il y a cinq ans de cela. Il était à la fois un juge au Sénégal, et un expert des droits de l'homme pour les Nations Unies. Ces mélanges viennent honorer sa mémoire. Les contributions sont signées d'anciens collègues experts ou juges, des juristes de tous les horizons et offrent une analyse approfondie de diverses questions de droits de l'homme et de droit international pénal, notamment la jurisprudence des juridictions pénales internationales, des champs d'intérêt pour feu le juge Kama.